Differential Proteomic Analysis by iTRAQ Reveals the Mechanism of Pyropia haitanensis Responding to High Temperature Stress - Jianzhi Shi; Yu‐Ting Chen; Yan Xu; Dehua Ji; Changsheng Chen; Chaotian Xie (2017)
Abstract Global warming increases sea temperature and leads to high temperature stress, which affects the yield and quality of Pyropia haitanensis . To understand the molecular mechanisms underlying high temperature stress in a high temperature tolerance strain Z-61, the iTRAQ technique was employed to reveal the global proteomic response of Z-61 under different durations of high temperature stress. We identified 151 differentially expressed proteins and classified them into 11 functional categories. The 4 major categories of these are protein synthesis and degradation, photosynthesis, defense response, and energy and carbohydrate metabolism. These findings indicated that photosynthesis, protein synthesis, and secondary metabolism are inhibited by heat to limit damage to a repairable level. As time progresses, misfolded proteins and ROS accumulate and lead to the up-regulation of molecular chaperones, proteases, and antioxidant systems. Furthermore, to cope with cells injured by heat, PCD works to remove them. Additionally, sulfur assimilation and cytoskeletons play essential roles in maintaining cellular and redox homeostasis. These processes are based on signal transduction in the phosphoinositide pathway and multiple ways to supply energy. Conclusively, Z-61 establishes a new steady-state balance of metabolic processes and survives under higher temperature stress.